Korban Pinjol, Layakkah sebagai Gharimin dan menerima zakat? - Syelvita, Rema; Amin Qodri, M.; Annisa Afro, Fakhriyah (Universitas Jambi, Fakultas Hukum, 2023)
This article discusses the controversial issue of victims of online lending (Pinjol) and whether they are eligible to receive zakat. Online lending has become a social problem affecting many people who are trapped in difficult debt situations. This discussion raises ethical and humanitarian aspects of assisting Pinjol victims. The fundamental question is what criteria make Pinjol victims eligible to receive zakat, a conventional form of assistance given to the poor and needy. The aim of this article is to explore the concept of victims in the context of online lending and consider the Islamic legal aspects related to the acceptance of zakat. The article provides an in-depth analysis of the impact of Pinjol on the financial lives of communities, considering factors such as interest rates, lending practices, and the psychological impact on borrowers. Furthermore, the article discusses the principles of Islamic Sharia related to zakat, such as the criteria for zakat recipients, justice, and debt management. The analytical method used is a qualitative descriptive approach, utilizing literature studies and Islamic legal perspectives on the status of Pinjol victims as gharimin (debtors). It is hoped that the results of this research will provide a clear understanding of whether those indebted to Pinjol can be considered victims and eligible for zakat. Additionally, this article can serve as a guide for zakat institutions, governments, and communities to develop more effective ways of providing assistance to those affected by the negative impacts of online lending.